1966
DOI: 10.1037/h0023229
|View full text |Cite
|
Sign up to set email alerts
|

Short-term verbal memory and learning.

Abstract: A number of paired-associate experiments are examined for evidence of the interaction of a short-term storage with a long-term learning mechanism. Differential effects depending on length of the retention interval are described for duration of the spacing interval between 2 presentations of individual pairs, duration of presentations, and number of repetitions. The rapidly decreasing initial portion of the retention curve with multiple paired associates is considered to be the result of interference and the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
45
0
1

Year Published

1967
1967
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 35 publications
5
45
0
1
Order By: Relevance
“…As is shown in Figure 7 (left panel), Zaromb et al (2005) reported that the boost in recall probability for a repeated item declined exponentially as more lists intervened between the list on which it originally appeared and the list on which it was repeated, until, after eight intervening lists, the recall probability approximated that of a new item. This pattern is consistent with research on spacing effects in that, although spaced repetition helps recall more than does massed repetition when there is a long retention interval following the second presentation, the reverse is true when the retention interval following the second presentation is short (Glenberg, 1977;Melton, 1963;Peterson, 1966;Peterson, Wampler, Kirkpatrick, & Saltzman, 1963). In Zaromb et al, recall always shortly followed the second presentation, and accordingly, there was better recall of more recently repeated items.…”
Section: Simulation 4: Effects Of Semantic Relations and Interlist Resupporting
confidence: 76%
“…As is shown in Figure 7 (left panel), Zaromb et al (2005) reported that the boost in recall probability for a repeated item declined exponentially as more lists intervened between the list on which it originally appeared and the list on which it was repeated, until, after eight intervening lists, the recall probability approximated that of a new item. This pattern is consistent with research on spacing effects in that, although spaced repetition helps recall more than does massed repetition when there is a long retention interval following the second presentation, the reverse is true when the retention interval following the second presentation is short (Glenberg, 1977;Melton, 1963;Peterson, 1966;Peterson, Wampler, Kirkpatrick, & Saltzman, 1963). In Zaromb et al, recall always shortly followed the second presentation, and accordingly, there was better recall of more recently repeated items.…”
Section: Simulation 4: Effects Of Semantic Relations and Interlist Resupporting
confidence: 76%
“…The uncommon generality and persistence of the spacing effect has led some investigators to propose that the phenomenon reflects the automatic operation of some fundamental memory process (e.g., Jensen & Freund, 1981) that may even be hard-wired into the memory system (e.g., Hintzm an, 1974;Landauer, 1969;Peterson, 1966). This hypothesis received support from a recent study by Cornell (1980), in which 5-and 6-month-old infants appeared to exhibit a spacing effect.…”
mentioning
confidence: 57%
“…Temporal effects in short-term memory (STM) have been studied by various methods, with conflicting results (Brown, 1958;Conrad & Hille, 1958;Corballis, 1966;Crowder, 1966;Mackworth, 1962;Norman, 1966;Peterson, 1966;Waugh & Norman, 1965). Two sources of difficulty in some studies of this problem may be restriction of retention and retrieval to some rather than all presented items, and possible confounding of temporal and interactional effects in retrieval with those in storage.…”
mentioning
confidence: 99%